Coastal carbon at risk: forecasting the impacts of sea-level rise on future land cover - Tahmasebi, Mojtaba; Bruck, Julie; Volk, Michael; Tepe, Emre; Alakshendra, Abhinav; Sadaf, Afsheen; Puleo, Jack A. (Frontiers in Ecology and Evolution, 2025)
IntroductionCoastal land cover (LC) is in constant flux and shaped by human activity and natural forces. These shifts have profound implications for climate resilience, as LC change can either enhance or diminish the landscape’s capacity to store and sequester carbon.MethodsThis study investigates the impact of sea-level rise (SLR) on carbon storage and sequestration within the coastal Superfund and industrially contaminated areas of Aberdeen Proving Ground (APG) and its adjacent environment, located in the northern Chesapeake Bay, Maryland. Leveraging the MOLUSCE plugin in QGIS and the InVEST model, this study integrates historical LC data with predictive modeling techniques, including artificial neural networks, multi-layer perceptron, and Cellular Automata.ResultsProjections for 2061 reveal that, under a no-SLR scenario and non-submerged aquatic vegetation (SAV) scenario, APG retains 4,059,312 Mg C in storage, losing -54,087 Mg C sequestration and -$42.06 million net present value (NPV). The NPV is changed to -$40.57 million for the Low SAV scenario and -$38.86 million for the High SAV scenario for 2061 under the no-SLR scenario. However, with SLR, storage declines to 3,894,892 Mg C, and sequestration losses escalate to -218,505.75 Mg C, representing -$169.93 million NPV for the non-SAV scenario. The amount of NPV is changed to -168.44 million and -$166.73 million for the Low and High SAV scenarios.DiscussionThese findings underscore the accelerating carbon debt imposed by SLR and the urgent need for adaptive strategies. Coastal preservation techniques, such as living shorelines and thin-layer placement, have emerged as critical strategies for mitigating carbon losses and enhancing resilience. By quantifying the ecological and economic consequences of SLR-driven LC change, this study advances the understanding of carbon dynamics in vulnerable coastal landscapes and reinforces the necessity of proactive management to sustain their climate-regulating functions.